2007
DOI: 10.1161/circulationaha.106.688889
|View full text |Cite
|
Sign up to set email alerts
|

Genes and Atrial Fibrillation

Abstract: A trial fibrillation (AF) is an abnormality of the heart's rhythm that is characterized by rapid and irregular activation of the atria. AF was first described in humans in 1906 1 and is now recognized to be the most common sustained cardiac arrhythmia and a major public health burden. 2 The loss of coordinated atrial contraction results in reduced ventricular filling and blood stasis in the atria, which predispose to heart failure and thromboembolic stroke, respectively. 3,4 AF accounts for 15% of all strokes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 87 publications
(108 reference statements)
0
24
0
Order By: Relevance
“…The coding regions were amplified using polymerase chain reaction and sequenced with a 3100 BigDye Terminator v3.1 sequencing kit and ABI PRISM 3100 Genetic Analyzer (Applied Biosystems, Foster City, CA, USA). We sequenced other AF-linked genes [ KCNE2 (NM172201), KCNE3 (NM005472), KCNE5 (NM012282), NPPA (NM006172), KCNA5 (NM002234), KCNJ2 (NM00891), GJA5 (NM005266 and 181703) , SCN1B (NM001037 and 199037), SCN2B (NM004588)] and SCN3B (NM018400) in the R231C-Q1 proband from the family with AF (Figure 1, Family A, subject II:1) (for review, see reference 1620 ). We also compared 21 single nucleotide polymorphisms (SNPs) (including KCNE5 ) that alter AF susceptibility (rs1805123, rs1805120, rs1805127, rs1805124, rs2200733, rs10033464, rs35594137, rs12621643, rs1800872, rs583362, rs7193343, rs3807989, rs11708996, rs6800541, rs251253, rs5063, rs13376333, rs11047543, rs3825214, rs1801252, and rs17003955) among the families shown in Figure 1 (Online Supplemental Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…The coding regions were amplified using polymerase chain reaction and sequenced with a 3100 BigDye Terminator v3.1 sequencing kit and ABI PRISM 3100 Genetic Analyzer (Applied Biosystems, Foster City, CA, USA). We sequenced other AF-linked genes [ KCNE2 (NM172201), KCNE3 (NM005472), KCNE5 (NM012282), NPPA (NM006172), KCNA5 (NM002234), KCNJ2 (NM00891), GJA5 (NM005266 and 181703) , SCN1B (NM001037 and 199037), SCN2B (NM004588)] and SCN3B (NM018400) in the R231C-Q1 proband from the family with AF (Figure 1, Family A, subject II:1) (for review, see reference 1620 ). We also compared 21 single nucleotide polymorphisms (SNPs) (including KCNE5 ) that alter AF susceptibility (rs1805123, rs1805120, rs1805127, rs1805124, rs2200733, rs10033464, rs35594137, rs12621643, rs1800872, rs583362, rs7193343, rs3807989, rs11708996, rs6800541, rs251253, rs5063, rs13376333, rs11047543, rs3825214, rs1801252, and rs17003955) among the families shown in Figure 1 (Online Supplemental Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…4 Thus, common genetic variants play a role in the development of this multifactorial disease. 5 Several studies have shown PR-interval prolongation on an ECG to be an independent risk factor for developing AF. [6][7][8] Five independent GWAS publications have shown that genetic variants in SCN10A influence the PR-interval duration.…”
Section: Clinical Perspective P 73mentioning
confidence: 99%
“…4 Thus, common genetic variants play a role in the development of this multifactorial disease. 5 Several studies have shown PR-interval prolongation on an electrocardiogram to be an independent risk factor for developing AF. 68 Five independent GWAS publications have shown that genetic variants in SCN10A influence the PR-interval duration.…”
Section: Introductionmentioning
confidence: 99%